Characteristics of Plastic Waste on Rivers in Hai Phong City, Vietnam - Thanh Nghi, Duong; Thu Huong, Do; Quoc Hai, Pham; Ngoc Hai, Dinh; Dac Ve, Nguyen; Thi Thu Ha, Nguyen; Thi Mai Huyen, Bui; Van Vuong, Bui; Hoai Nhon, Dang; Van Quy, Tran (VNU Journal of Science: Earth and Environmental Sciences, 2025)
In this research, we conducted three complementary survey methods including visual observation, underwater sampling with nets, and riverside sampling with quantitative plots with six plastic waste monitoring stations on the river in Hai Phong city: An Thai, Tram Bac, Kien An, Bui Vien, Rao, Tan Vu Lach Huyen to study the plastic waste on rivers. We found the most concentrated plastic waste in the city was at Bui Vien station (1,239 objects 33.05%) and Rao station (938 objects, 25.05%). During the four months of monitoring plastic waste on the rivers in Hai Phong city (November, December of 2024 and June, August of 2025), the total amount of plastic waste collected was 3,749 objects. The amount of plastic waste in the dry season is higher than in the wet season, respectively 54.41% and 45.59%. In the nine groups of plastic waste monitored, nylon bags and packaging plastic bags account for the majority, at 24.03% and 35.48% respectively. Plastic waste with low proportion is beverage and food waste (6.68%), hygiene and sanitary waste (1.48%), fishing net and aquaculture waste (2.97%), miscellaneous items waste (8.13%), items of unidentifiable origin waste (13.44%), and other types of plastic waste (1.03%). The total amount of plastic waste will be highly concentrated in the dry season, accumulating in the urban center over the years and the number of types of plastic waste that need to be prioritized for treatment and management so that the urban can develop in the direction of a green, clean, smart, cultural and modern urban area.